Оптические и люминесцентные свойства монокристаллов YAG:Ce облученных ионами Xe132 с энергией 231 МэВ - Баубекова, Гулдар; Турсумбаева Г.; Асылбаев Р.; Карипбаев Ж.; Кисабекова А.; Акилбеков А.Т. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2025)
The study investigates the effect of 230 MeV xenon ion irradiation on the optical and luminescent properties of Y3Al5O12:Ce (YAG:Ce) crystals. Irradiation leads to the formation of Frenkel defects (F, F+), antisite defects, as well as the suppression of Ce3+ ion emission due to the intensification of nonradiation processes and charge transfer Ce3+ Ce4+ . It is shown that with increasing fluence, the luminescence intensity of Ce3+ decreases as a result of the formation of crystals lattice defects such as oxygen vacancies and antisite disorders. Changes in the valence state of cerium (Ce3+ Ce4+) are also possible. The obtained results provide insight into radiation-induced processes in YAG:Ce, which are important for its application in radiation-resistant scintillation detectors.